Analisis Yuridis Keterangan Saksi Testimonium De Auditu dalam Surat Pernyataan Sporadik Penguasaan Tanah Perspektif Kepastian Hukum - I Gede Ngurah Budi Eka Prayusa; Yogi Yasa Wedha; I Made Kariyasa (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
Land registration through the substantiation of prior rights may be conducted on the basis of physical possession for 20 years or more, as evidenced by a sporadic statement letter and witnessed by at least two witnesses. However, this provision creates an opportunity for the use of testimonium de auditu, namely testimony based on hearsay that cannot be materially verified. In practice, the assessment of proof of prior rights as regulated under Article 24 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration contains the phrases “degree of truth” and “deemed sufficient” without clear parameters, thereby giving rise to legal uncertainty. This normative juridical research employs the theory of legal certainty and the theory of evidence to analyze two principal issues: the regulation of land registration in Indonesia and the evidentiary strength of de auditu testimony. The findings indicate that de auditu testimony does not meet the criteria of valid witness evidence and fails to provide legal certainty, while the ambiguity of the norm necessitates further regulatory clarification.